Relationship between accounting earnings, cashflows and stock prices of service sector in Malaysia stock market - Cheng, Fan Fah; Siew, Kuan Por; Md Nassir, Annuar; Cheng, Seow Voon (American Scientific Publishers, 2018)
There had been evidences reported that the accounting earnings and cash flows have information content for stock valuation. However, it is still questionable on whether cash flows have incremental information content beyond earnings disclosures. This paper examines the relative information content of earnings and cash flows in explaining stock returns. By employing a sample of service companies from the years 2002 to 2013, the study adds evidence on the impact of accounting earnings and cash flows on annual stock returns of Malaysian public listed companies. Earnings are found to have more significant impact on stock returns and demonstrate a stronger degree of positive association with the stock returns. Among the three components cash flow, investing cash flows are found to have weak influence on the stock returns. The findings suggest that earnings have greater explanatory power for stock returns than cash flows and the cash flows have weak incremental information content beyond earnings. In general, the investors tend to value stock prices of the service companies using earnings rather than cash flows in the services sector.